2018
DOI: 10.1371/journal.pone.0209928
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic protocol for microinjection-related handling of Siberian sturgeon (Acipenser baerii; Acipenseriformes) prolarvae

Abstract: An anesthetic protocol was optimized for microinjection-related handling of Siberian sturgeon (Acipenser baerii; Acipenseriformes) prolarvae, an extant primitive fish species commonly grown in aquaculture. Comparative examinations of three selected anesthetics (clove oil, lidocaine, and MS-222) with a dosage regime of 50, 100, 200, and 400 mg/L indicated that MS-222 was the most efficient agent for Siberian sturgeon prolarvae, as evidenced by the fast induction of anesthesia with quick and uniform recovery. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…During the early ontogenetic period (1 to 3 dph), showing an initial increase in the expression of AbSOD1 (and AbSOD2), A. baerii prelarvae change their behavior from drifting movement to active pelagic swimming at the upper water column, with dramatic increases in swimming distance and speed. Furthermore, prelarvae during this period have the strongest positive phototaxis, making them continuously pursue light sources [ 61 ]. Undoubtedly, such energy-intensive behavioral changes are accompanied by an increased respiration rate and parallel accumulation of oxygen radicals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the early ontogenetic period (1 to 3 dph), showing an initial increase in the expression of AbSOD1 (and AbSOD2), A. baerii prelarvae change their behavior from drifting movement to active pelagic swimming at the upper water column, with dramatic increases in swimming distance and speed. Furthermore, prelarvae during this period have the strongest positive phototaxis, making them continuously pursue light sources [ 61 ]. Undoubtedly, such energy-intensive behavioral changes are accompanied by an increased respiration rate and parallel accumulation of oxygen radicals.…”
Section: Discussionmentioning
confidence: 99%
“…However, one plausible explanation is that the continuous increase in this isoform might be partially related to neovascularization and increased circulation activities in developed blood vessels, rather than to the defense against the overall oxidative stress caused by high-oxygen-consuming exercise. Previous studies have indicated that A. baerii hatchlings usually continue vasculogenesis/angiogenesis during the prelarval period, especially associated with the active development of the external gill filaments and branchial circulation [ 39 , 40 , 42 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Test species and procedure A total of 260 number of larvae of D. carneus were used for the entire study. The larvae were anesthetized using MS222 before the study procedures [116,117] . Different larval stages and juveniles stages were photographed appropriately.…”
Section: Ethics Statementmentioning
confidence: 99%
“…In hatcheries, sturgeon prelarvae are generally expected to experience substantial changes of light intensities according to the diel photoperiodicity, suggesting that the practical guide for prelarval nursery should essentially consider the photobehavior of prelarvae. Furthermore, the comprehensive guideline of behavioral ontogeny may also be a fundamental basis for various research investigations with prelarvae such as ontogenetic gene expression assay and examination of physiological alterations, because all those investigations need the information on the standard behavioral phenotype of experimental specimens used (Song et al, 2016;Kim and Nam, 2018;Kim et al, 2019c).…”
mentioning
confidence: 99%